Choral music on record - Blyth, Alan (Cambridge University Press, 1990)
Following the successful volumes of Song on Record, this 1991 book surveys all the recordings of major choral works from the Monteverdi Vespers to Britten's War Requiem. Discussion of the various interpretations on record is preceded, in each chapter, by informed criticism of the work concerned, including - where appropriate - a clarification of editions, revisions, etc. (all the many changes in Messiah are, for instance, described in detail). The coverage of recordings is exhaustive and its value is enhanced by detailed discographies, with numbers of each recording. Each contributor is an authority within his or her specialist area and, collectively, their insights and observations make the book invaluable to record collectors, music lovers and all with an interest in changing tastes and styles of musical performance
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Choruses / Discography; Sound recordings / Reviews; Tonträger; Chormusik; Aufsatzsammlung